Serat gumuyu: Sumber pengaruh untuk membentuk persepsi kebahagiaan dan kesehatan mental masyarakat - Agil Alhaidar, Muhammad Said; Widodo, Widodo (Aksara: Jurnal Bahasa dan Sastra, 2024)
The manuscript is one of the cultural relics of the past which is a source of cultural institutions of the community. The manuscript is also used as a reflection of local wisdom and a foundation for oral traditions, art, and Javanese values, as is the case with the Serat Gumuyu script. This study uses a qualitative descriptive approach to obtain complete information about laughter can shape the perception of each individual to manage a more positive mindset so as to form happiness and improve people's mental health from Serat Gumuyu. The theory used is Seligman's mental health theory, which focuses on the psychological aspects of mental health and which focuses on positive psychological theories, especially happiness. This research data is in the form of quotes derived from Serat Gumuyu. The source of this research data is Serat Gumuyu, serial number NB 1567 code obtained from manuscripts in the collection of the National Library of the Republic of Indonesia. The data collection method uses content analysis techniques to describe the manuscript, editing and transliteration. The text is hermeniutic analyzed by Ricoeur to explore the axis of the roots of cultural forces socially and mental health in Javanese society. This research presents how laughter in Serat Gumuyu contains the benefits and factors that make someone laugh. This serat invites us that the positive influence of laughter can provide many benefits and is not visible physically but in human mental health also becomes better and optimal.Keywords: Serat Gumuyu, laugh, mental health